Mechanisms for Alternaria alternata Function in the Skin During Induction of Peanut Allergy in Neonatal Mice With Skin Barrier Mutations - Buelow, Lauren M.; Hoji, Akihiko; Tat, Kiet; Schroeder-Carter, Lindsay M.; Carroll, Daniela J.; Cook-Mills, Joan M. (Frontiers in Allergy, 2021)
Neonatal mice with heterozygous mutations in genes encoding the skin barrier proteins filaggrin and mattrin (flaky tail mice [FT+/-]) exhibit oral peanut-induced anaphylaxis after skin sensitization. As we have previously reported, sensitization in this model is achieved via skin co- exposure to the environmental allergen Alternaria alternata (Alt), peanut extract (PNE) and detergent. However, the function of Alt in initiation of peanut allergy in this model is little understood. The purpose of this study was to investigate candidate cytokines induced by Alt in the skin and determine the role of these cytokines in the development of food allergy, namely oncostatin M (Osm), amphiregulin (Areg) and IL-33. RT-qPCR analyses demonstrated that skin of FT+/- neonates expressed Il33 and Osm following Alt or Alt/PNE but not PNE exposure. By contrast, expression of Areg was induced by either Alt, PNE or Alt/PNE sensitization in FT+/- neonates. In scRNAseq analyses, Osm, Areg and Il33 were expressed by several cell types, including a keratinocyte cluster that was expanded in the skin of Alt/PNE-exposed FT+/- pups as compared to Alt/PNE-exposed WT pups. Areg and OSM were required for oral PNE-induced anaphylaxis since anaphylaxis was inhibited by administration of neutralizing anti-Areg or anti-OSM antibodies prior to each skin sensitization with Alt/PNE. It was then determined if intradermal injection of recombinant IL33 (rIL33), rAreg or rOSM in the skin could substitute for Alt during skin sensitization to PNE. PNE skin sensitization with intradermal rIL33 was sufficient for oral PNE-induced anaphylaxis, whereas skin sensitization with intradermal rAreg or rOSM during skin exposure to PNE was not sufficient for anaphylaxis to oral PNE challenge. Based on these studies a pathway for IL33, Areg and OSM in Alt/PNE sensitized FT+/- skin was defined for IgE induction and anaphylaxis. Alt stimulated two pathways, an IL33 pathway and a pathway involving OSM and Areg. These two pathways acted in concert with PNE to induce food allergy in pups with skin barrier mutations.